Innovative frequency and voltage controller for AC microgrid - Xuan Hoa Thi Pham; Hai Van Tran (International Journal of Power Electronics and Drive Systems (IJPEDS), 2026)
This paper designs a power controller for power converters using fuzzy logic. The proposed controller will automatically adjust the frequency and voltage when the load changes to improve the power quality of the microgrid. Besides, the controller can realize accurate power sharing among the power converters in the microgrid, thereby suppressing the circulating current between the inverters. Furthermore, to ensure the control system operates stably and accurately during voltage and frequency adjustments, this paper employs a sliding-mode controller rather than a conventional proportional-integral controller. The proposed control method has a voltage deviation from the rated value when the load changes in the range of 1.5 Volts to 2.7 volts, and a frequency deviation from the rated value when the load changes in the range of 0.2 to 0.4 Hz. The accuracy of reactive power division is 100%. The proposed controller is simulated using MATLAB/ Simulink software, and the results obtained from the simulation have verified the effectiveness of the proposed method.